2023
DOI: 10.1186/s12885-023-10888-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cervical intraepithelial neoplasia grade 2 or worse in women aged ≥ 69 referred to colposcopy due to an HPV-positive screening test

Abstract: Background Cervical cancer incidence and mortality rates are high in older women in many developed countries, including Denmark. Therefore, Danish women aged 69 and older were invited for one additional human papilloma virus (HPV) based screening test in 2017. Here, we describe the clinical management and detection rate of cervical intraepithelial neoplasia grade 2 or worse (CIN2 +) in screen-positive women referred for colposcopy. Methods We condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A recent observational study conducted in Denmark also revealed that most women (74.9%) have TZ3 at colposcopy, and 20.0% of women had CIN2 + diagnosed among women aged ≥ 69 referred to colposcopy due to an HPV-positive screening test. The findings also suggested a potential risk of underdiagnosis of CIN2 + in older postmenopausal women referred to colposcopy [ 24 ]. Additionally, Gustafson et al [ 11 ] found that CIN2 + detection is underestimated when comparing the proportion of CIN2 + in cervical biopsies with that in large loop excision of the transformation zone (LLETZ) specimens in women aged ≥ 45 years with TZ3.…”
Section: Discussionmentioning
confidence: 99%
“…A recent observational study conducted in Denmark also revealed that most women (74.9%) have TZ3 at colposcopy, and 20.0% of women had CIN2 + diagnosed among women aged ≥ 69 referred to colposcopy due to an HPV-positive screening test. The findings also suggested a potential risk of underdiagnosis of CIN2 + in older postmenopausal women referred to colposcopy [ 24 ]. Additionally, Gustafson et al [ 11 ] found that CIN2 + detection is underestimated when comparing the proportion of CIN2 + in cervical biopsies with that in large loop excision of the transformation zone (LLETZ) specimens in women aged ≥ 45 years with TZ3.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a new, rather large, patient collective in the German cervical cancer screening has led to a high influx of patients in all centres for colposcopy. This anticipated elevated colposcopy referral rate, after the introduction of HPV screening on the one hand and the reduced sensitivity rates of colposcopy in patients with a T3 transformation zone on the other hand, poses a major controversy [13,14,35]. Endocervical curettage is often uncomfortable or painful for the patients, and the rates of additional CIN2+ diagnosis are only between 0.8 and 6% [36].…”
Section: Discussionmentioning
confidence: 99%
“…With the ageing population globally, it is anticipated to represent a growing issue in the forthcoming decades. As in the case of a type 3 transformation zone (TZ), only limited assessment of the transformation zone is possible; this may result in an increased risk of missing disease by up to twofold [12][13][14]. To improve the detection and reduce the risk of missing disease in this group of women, endocervical curettage (ECC) can be performed but remains controversial [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the performance of these methods may vary depending on the prevalence and distribution of HPV types and the stage and grade of cervical lesions. In clinical practice, the patients with cervical lesion CIN2 or worse including CIN2, CIN3, and cancer (CIN2+) are at high risk of developing cancer and need active surveillance or treatment 17 , 18 . Consequently, there is a need for more context-specific guidelines for the optimal screening and detection strategies for cervical lesions.…”
Section: Introductionmentioning
confidence: 99%